The Academic Spoken Word List. Issue 4 (14th September 2017) - Dang, Thi Ngoc Yen; Coxhead, Averil; Webb, Stuart
Abstract: The linguistic features of academic spoken English are different from those of academic written English. Therefore, for this study, an Academic Spoken Word List (ASWL) was developed and validated to help second language (L2) learners enhance their comprehension of academic speech in English‐medium universities. The ASWL contains 1, 741 word families with high frequency and wide range in an academic spoken corpus totaling 13 million words. The list, which features vocabulary from 24 subjects across four equally sized disciplinary subcorpora, is graded into four levels according to Nation's British National Corpus and Corpus of Contemporary American English lists, and each level is divided into sublists of function words and lexical words. Depending on their vocabulary levels, language learners may reach 92–96% coverage of academic speech with the aid of the ASWL. Open Practices: This article has been awarded Open Materials and Open Data badges. The composition of the corpora, the Academic Spoken Word List, and sublists are publicly accessible via the Open Science Framework athttps://osf.io/gwk45 and the IRIS digital repository athttp://www.iris‐database.org . Learn more about the Open Practices badges from the Center for Open Science:https://osf.io/tvyxz/wiki .